A Straightforward Procedure to Select Passive Elements in Single-phase Pulse-width Modulation Rectifiers with Developed Resonant Current Controller. Issue 4 (25th February 2016) - Pichan, Mohammad; Ahamad, Ahmad Ale; Arishamifar, Adib; Jamarani, Mohammad Ebrahimi
Abstract: With increasing DC loads, single-phase pulse-width modulation rectifiers have been used widely. In this article, based on a mathematical model and equations of a system, a new straightforward procedure is developed to calculate input filter inductance and output filter capacitance values. To avoid filter overdesign, which results in higher cost and size, this procedure is useful and helps design engineers to select the filter passive elements values properly and simply. The proposed procedure is subjected to set inductor current and capacitor voltage ripple at their acceptable range. Moreover, an improved current controller based on a proportional-resonant controller is developed. This controller can remove specific input current harmonic components, which results in lower total harmonic distortion for input current. A 4-kW prototype is provided based on a digital signal processor (DSP)-based digital controller to support all of the theoretical analyses. Several simulations and experimental results verify the effectiveness of the developed current controller at both steady-state and dynamic conditions. Also, the results verify the validation of the developed procedure in maintaining the voltage and current ripple at their expected values.